Herbicides and Cereal Rye for Palmer Amaranth Management in Corn and Soybean - Igor G. R. Lima; Alec C. Adam; Wade T. Burris; Salina Raila; Sarah Lancaster (Kansas Agricultural Experiment Station Research Reports, 2024)
Palmer amaranth control is a substantial problem for corn and soybean producers in the United States. Farmers are increasingly interested in cover crops a tool to manage this troublesome weed. Studies were conducted at Rossville, Kansas, in 2023, to assess the most effective combination of herbicides and cereal rye cover crop termination time to control Palmer amaranth in corn and soybean. Treatments that included atrazine + an HPPD-inhibiting herbicide + a VLCFA-inhibiting herbicide plus glyphosate provided the greatest weed control in corn. For soybeans, the combination with the greatest weed control was a PPO-inhibiting herbicide + a VLCFA-inhibiting herbicide + an ALS-inhibiting herbicide plus glyphosate.
Keywords: integrated; weed management; combination; cover crop